Climate-energy-water nexus in Brazilian oil refineries. (November 2019) - Guedes, Fernanda; Szklo, Alexandre; Rochedo, Pedro; Lantz, Frédéric; Magalar, Leticia; Arroyo, Eveline Maria Vásquez
Highlights: Oil refineries are energy-intensive, major CO2 emitters and are usually located in water-stress sites. Oil refining activity requires large amounts of water, which varies according to the process configuration. CO2 mitigation options can reduce water withdrawals, can increase it, or be neutral. Abstract: Oil refineries are major CO2 emitters and are usually located in water-stress sites. While some CO2 mitigation options can reduce water demand, others can increase it, and still others are neutral. By simulating two parametric models, one for all Brazilian refineries, and the other locally detailing the water balance of the country´s largest refinery, this study aimed to quantify the impacts of CO2 mitigation options on the water use of oil refineries. Findings show that, by pricing CO2 emissions up to 100 US/tCO2, the list of mitigation options was able to abate 25% of the annual emissions in Brazilian refineries. A relevant share of this abatement derives from the implementation of carbon capture (CC) facilities in fluid catalytic cracking and hydrogen generation units. However, these CC facilities offset the co-benefits of other CO2 mitigation options that can reduce steam and cold-water requirements in refineries. In fact, for the largest Brazilian oil refinery, the implementation of all mitigation measures had almost no effect on its water balance. This means that CO2 abatement in refineries has no significant impact on water demand (no negative trade-off). However, this also means that the water stress in oil refineries should be dealt with measures not directly linked to CO2 abatement (no significant co-benefits).